Repurchase intention of fresh food online shopping amid Covid-19 pandemic - Fajrin Rimadhyani Firdaus; Nurdin Sobari (President University, 2022)
Covid-19 has shifted Indonesia consumer’s shopping behavior; it shifted from offline shopping to online shopping. One of the online shopping categories that has increased during the Covid-19 pandemic is grocery shopping. This study integrates the role of post-purchase online customer experience by analyzing consumer perception to intensify their repurchase. This study aims to investigate how repurchase intention is influenced by post-purchase online customer experience, customer satisfaction, and trust in e-commerce. An online survey was conducted in Indonesia to capture fresh food online shoppers as participants. SEM AMOS was utilized to test the research model with eight hypotheses and analyzed data collected from 605 respondents. This study shows that four post-purchase OCE dimensions, “delivery, packaging, return and exchange, and customer support, significantly drive customers’ satisfaction. “Benefits and product in hand” is not influential. Customer satisfaction is found as a significant contributor to trust. Additionally, trust revealed has a significant impact to repurchase intention. The result of this study suggests that sellers in e-commerce need to consider delivery, packaging, ease of return and exchange, and responsive customer support to retain their customers